One Pot Synthesis and Antibacterial Activity of 3,5-Dibromo-2,4-dihydroxy Substituted Chalcones - Devpura, Anju; Sharma, Parul; Singh Chundawat, Sumer; Shaktawat, Sheetal; S. Dulawat, Shiv (Asian Journal of Chemistry, 2011)
In an effort to develop antibacterial agents, a series of chalcones were prepared by Claisen- Schmidt condensation of appropriate acetophenones with appropriate aromatic aldehydes in the presence of basic alumina as solid support reagent under microwave irradiation. The synthesized compounds were characterized by their IR, 1H NMR, mass spectral data and elemental analysis. The compounds have been screened for their antibacterial activity against S. aureus, S. fecalis, E. coli and P. mirbilis.